2021
DOI: 10.31436/iiumlj.v29i1.609
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Flogging as a Punishment in Saudi Arabia From the Perspective of International Human Rights Law

Abstract: Flogging is one of the most widely-used corporal punishments in Islamic penology. Most countries that practice Islamic criminal law use flogging to punish a variety of crimes and offenses. Saudi Arabia is one of the countries that use flogging to punish various crimes and has faced immense backlash from the international community for gross violation of human rights. The goal of this article is to investigate the implementation of flogging as a punishment in Saudi Arabia. Moreover, it also examines how interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This is mainly because the flogging is done in the open, not secrete. This finding supports Sebar and Ismail (2021), who reported that public flogging against alcohol misuse in Saudi Arabia was done publicly. The media coverage given to public flogging, especially on social media pla orms in the Southeast, may have given it visibility.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is mainly because the flogging is done in the open, not secrete. This finding supports Sebar and Ismail (2021), who reported that public flogging against alcohol misuse in Saudi Arabia was done publicly. The media coverage given to public flogging, especially on social media pla orms in the Southeast, may have given it visibility.…”
Section: Discussionsupporting
confidence: 87%
“…However, public flogging as a deterrent against an -social behaviour is mainly used in Islamic countries; for instance, Indonesia (Panjaitan & Tjandra, 2022) and Afghanistan (France 24, 2010). In addi on, Saudi Arabia (Sebar & Ismail, 2021) reported that with the prohibi on of alcohol consump on, offenders are sanc oned through public flogging. Similarly, in Northern Nigeria, with Islam as the dominant religion, there have been several occurrences of public flogging for offenses such as smoking marijuana, adulter y/fornica on, indecent dressing, etc.…”
Section: Public Flogging As a Control Measurementioning
confidence: 99%
“…In international justice, the ability to invoke and applylaws is also the main symbol of the effectiveness of international law. According to the summary of the researchers,the main theories based on the utility of international law include the theoryof natural law, the theory of basic rights, the theory of common will, thetheory of state self-restraint, the theory of sacredness of international contracts,the theory of international relations, and the theory of state needs [ 3 ]. However, no matter which theory is adopted, itspurpose proves that international law is reasonable from a certain side orangle.…”
Section: Introductionmentioning
confidence: 99%
“…A more nuanced defense of international pessimism is that international morality is impossible due to certain structural elements of anarchical world order The theoretical argue that ethical standards must be justified by demonstrating how adhering to them advances the long-term interests of each the representative to who they apply, combined with the direct claim that the global state of their nature is a state of war, constitute the two premises of the Hobbesian argument against international skepticism , One major reason for doubting the viability of international political theory is that it will disappear if the author's critique of the Hobbesian understanding of international relations is valid. A convincing argument for the viability of international political philosophy does not reveal much about the ideas that underpin it Sebar, H., & Ismail, S. M. (2021) [2].…”
Section: The Foundations Of International Relationsmentioning
confidence: 99%